The scientific thinking in Islam: factors of flourishing and decline - Shogar, Ibrahim (IIUM Press, 2011)
The role played by science and technology for the development of human society is crucial in the modern age. Contemporary Muslim societies, without scientific thinking, have little chance to progress. The quality of live, in the globalized world, is based on the intellectual value of the mind. The Holy Qur`an launched its glorious mission by “Iqra” due to the fact that the quality of thought directly affects the quality of action; and both of them affect the quality of live. At the opening of its golden age around the eighth century, and nearly for a thousand years, the Islamic civilization remained creative in science, technology and arts. The achievements of Muslim scientists surpassed all their contemporaries. The scientific worldview of Islam was the inspiring force of their inquiry and pursuit of knowledge. At that time the Muslim world was ranged from Spain and Morocco, through Damascus, Cairo and Baghdad, to Persia and North India. However, starting around the sixteenth century, the Islamic civilization began to wane; losing ground to other nations. Today, Muslim communities are struggling for development within the global challenges, especially scientific and technological challenges. There are many questions that need to be addressed by modern Muslim intellectuals: (1) What were the main factors behind the flourishing of science and technology in the early history of Islamic civilization? (2) What were the main causes of decadence of the scientific thinking? (3) How could Muslims restore their creative thinking again? The main objective of this work is to shed some light upon these questions.